Modeling principles of the digital infrastructure of it services in sustainable low carbon transport systems - Yu. V, Trofimenko; A G, Nekrasov; A S, Sinitsyna; K I, Atyev (International Journal of Engineering and Technology, 2018)
The principles of adaptive management of sustainable low carbon transport systems (SCTS) are developed based on the interaction of intellectual and Internet technologies, which ensure the effectiveness of core elements of the system throughout the life cycle of digital infrastructure and IT services. The technologies of proactive (anticipatory) management are accompanied by targeted procedures for reconfiguring the structures of transport system, and provide a comprehensive forecast of the system's behavior and increase its efficiency on the basis of a large array of digital data. The 4D model of SCTS transformation into the digital environment is developed, which allows integrate the most important modules of the transport system, ensuring highly efficient interaction of various objects in the interest of customers.Â Â